Return to sports following arthroscopic Bankart repair: a narrative review - Shafira Widya Utami; Savina Rifky Pratiwi; Mitchel; Karina Sylvana Gani; Erica Kholinne (The Ewha Medical Journal)
A Bankart lesion is a tear of the labrum, the ring of cartilage that encircles the shoulder joint socket, that can occur when the shoulder is dislocated. This injury frequently affects young athletes and is associated with shoulder instability. This review was performed to provide an overview of anterior shoulder instability, with an emphasis on rehabilitation and the return to sports following arthroscopic Bankart repair. We searched the Google Scholar and PubMed academic databases through February 18th, 2024, utilizing keywords including “arthroscopic Bankart repair” and “return to sports”. Our findings indicate that athletes who undergo arthroscopic Bankart repair exhibit higher rates of returning to sports compared to those who receive other anterior shoulder stabilization procedures. Several factors are considered when determining readiness to return to athletics, including time elapsed since surgery, type of sport, strength, range of motion, pain, and proprioception. Surgeons typically advise athletes to wait approximately 6 months after surgery before resuming sports activities. They also recommend that athletes regain at least 80% of the strength of the uninjured shoulder or achieve strength levels comparable to those prior to the injury. Additionally, patients are expected to attain a full range of motion without pain, which should be symmetrical to the uninjured side, and demonstrate improved proprioception in the shoulder. The sport in which an athlete participates can also influence the timeline for return. Those involved in overhead sports, like baseball or tennis, often experience lower success rates in returning to their sport compared to athletes from other disciplines.